Unique Nutcracker Phenomenon Involving the Right Renal Artery and Portal Venous System. (1st July 2014) - Stephens, Maximilian; Ryan, Sarah Kate; Livsey, Roger
Abstract : The nutcracker phenomenon is usually caused by compression of the left renal vein by the superior mesenteric artery anteriorly and the aorta posteriorly, although variations of this anatomy have previously been reported. We observed a nutcracker phenomenon in a 42-year-old female who underwent portal venous phase computed tomography of the body for oncologic workup. She had no documented proteinuria or hematuria. Multiplanar reconstructions demonstrated an enhancing left renal vein draining into the left ovarian vein without draining into the inferior vena cava due to external compression immediately before the renocaval junction. The left renal vein was compressed between the right renal artery and the portal vein. This type of nutcracker has not been previously reported in the literature and represents a new variation.